TINJAUAN TENTANG JUAL BELI UANG RUSAK DALAM PERSPEKTIF PASAL 1320 KITAB UNDANG-UNDANG HUKUM PERDATA (STUDI KASUS DI PASAR KODIM KECAMATAN SENAPELAN KOTA PEKANBARU) - Umary, Fajrika Adil; Bachtiar, Maryati; Putra, Setia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Buying and selling damaged money (Bakul Duit Keliling) is a transactionactivity of buying and selling damaged money to people who have damagedmoney and replacing it with half or more than half the nominal amount ofdamaged money owned by the community. Therefore, the aim of this thesisresearch is first, the buying and selling of damaged money that occurs at theKodim Market, Senapelan District, Pekanbaru City is in accordance with thelegal terms of the agreement. Second, the legal consequences of buying andselling damaged money that occurred at the Kodim Market, Senapelan District,Pekanbaru City from the perspective of Article 1320 of the Civil Code.The type of research that the author uses is Sociological legal research.The research location was carried out at the Kodim Market, Senapelan District,Pekanbaru City. Meanwhile, the population and sample are all parties related tothe problem examined in this research, the data sources used, primary data andsecondary data, data collection techniques in this research using interviews,literature review and data analysis.As for the results of the research problem, there are two main things thatcan be concluded. Firstly, buying and selling damaged money at the SenapelanDistrict Kodim Market involves mobile Money Baskets (Buyers of DamagedMoney) and traders selling at the Senapelan District Kodim Market. Second, thelegal consequences of buying and selling damaged money that occurred at theKodim Market, Senapelan District, Pekanbaru City, are null and void.Keywords : Agreement - Buying and Selling Damaged Money - LegalConditions